Extraction and quantification of toxic compound mimosine from leucaena leucocephala leaves - Ilham, Zul (Elsevier, 2015)
The existence of mimosine in Leucaena leucocephala prevents the utilization of its biomass residues (after energy conversion) as animal feed. In this study, mimosine quantification in Leucaena leucocephala was carried out by using rapid colorimetric method. In addition, two different extraction methods which are soxhlet extraction with either distilled water or ethyl acetate as extraction solvent and digestion method were used to compare its efficiency in extracting the mimosine from Leucaena leucocephala leaves. The samples from both extraction methods were then clarified by boiling it with 30 mg activated carbon and filtered. The absorbance of diluted aliquot of 1-2-3-4-5 mL was then obtained from spectrophotometer at the wavelength of 535 nm. The concentration of mimosine from soxhlet extraction with distilled water was found to be higher compared to the digestion method but in contrast with ethyl acetate solvent extraction.